FUNGSI LEGISLASI DPD DALAM SISTEM KETATANEGARAN INDONESIA - STEVANUS EVAN SETIO (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
The legislative institution representing the majority of the people and the governmentis responsible to him. In order to reform the structure of the legislative institution inIndonesia into two rooms (bicameral) consisting of the House of Representatives(Dewan Perwakilan Rakyat (DPR)) and the Regional Representative Council (DewanPerwakilan Daerah (DPD)). By the bicameral structure of the legislation process isexpected to be held by double checking system that allow representation of theinterests of all the people can be achieved relatively wider social base through.Legislation function, related to the authority determine, the rules that bind andrestrict citizens to the legal norms. The Regional Representative Council (DewanPerwakilan Daerah (DPD)) function, which is supposed to be a counterpart to thepower of the House of Representatives (Dewan Perwakilan Rakyat (DPR)), looks nomore than “accessories” representation system in Indonesia, which is still thick withunicameral system. Bicameral representation system adopted in the composition ofrepresentative institutions Indonesia can be categorized as a soft bicameral system.With a power as given by the constitution of Indonesia, the Regional RepresentativeCouncil (Dewan Perwakilan Daerah (DPD)) as a representation of the regionalpeople’s institution do not yet get the goal at the purpose of this institutionestablishment.